Human immuno-deficiency virus and hepatitis B virus coinfection in pregnancy at the University College Hospital, Ibadan (2010)
Human Immuno-deficiency virus (HIV) and Hepatitis B Virus (HBV) share common modes of transmission which include blood borne and the vertical routes. Although, the natural course of HTV does not appear altered by HBV, the rate of liver-related deaths is several times higher among HIV/HBV co-infected persons. Clinicians providing care for HIV positive individuals, including pregnant women, need to be aware of this problem. This is a 2-year cross-sectional study that commenced in January 2006, among HIV positive pregnant women seen at the University College Hospital, Ibadan. During the study period, 721 HIV positive pregnant women were screened for hepatitis B virus infection. Sixty-four women (8.9%) were positive for HBsAg, 14(1.9%) were HCV positive and 642 (89.2%) were negative for both HBV and HCV. One patient was positive for both HBV and HCV. There were no remarkable differences between HIV infected and IIIV-HBV coinfected patients in terms of the hematological, albumin and bilirubin measurements. Alanine transaminase was however higher in the HIV-HB V co-infected patients than HIV patients and this was statistically significant (17.5 iu/ ml vs. 15.0 iu/ml, p value- 0.009). In addition, the CD4 cell count was lower and the viral load marginally higher in the hepatitis B virus positive patients. The differences were however not statistically significant (p value- 0.114 and 0.644 respectively). HIV- HBV co-infection in HTV positive pregnant women is not of negligible proportions as demonstrated in this study. Thus, HIV positive pregnant women should be screened for HBV and assisted to access care targeted at preventing morbidity and vertical transmission.